Preferences and Decision Support in Competitive Bidding - Nicolas Fugger; Philippe Gillen; Alexander Rasch; Christopher Zeppenfeld (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We examine bidding behavior in first-price sealed-bid and Dutch auctions, which are strategically equivalent under standard preferences. We investigate whether the empirical breakdown of this equivalence is due to (non-standard) preferences or due to the different complexity of the two formats, i.e., a different level of mathematical or individual sophistication. First, we elicit measures of individual preferences and secondly manipulate the degree of complexity by offering various levels of decision support. Our results show that the equivalence of the two auction formats only breaks down in the absence of decision support. This indicates that the empirical breakdown is caused by differing complexity between the two formats rather than non-standard preferences.
Keywords: D44; D81; D47; 330